MENINGKATKAN KUALITAS PEMBELAJARAN DI UPTD SDN KELEYAN 1 KECAMATAN SOCAH MELALUI SETRATEGI SOPIMESEM - Subakir Subakir (re-JIEM (Research Journal of Islamic Education Management), 2019)
The quality of education is realized through a quality learning process. Quality learning outcomes are quality student learning outcomes as well. Quality learning outcomes are learning outcomes in the form of critical thinking skills, innovative creative, communicative, and collaborative. This school action research was conducted to overcome the low quality of learning in UPey SDN Keleyan 1 Socah District. Sopimesem strategy was chosen as an alternative to overcoming the problem. With the research objectives: 1) Assessing the application of the Sopimesem strategy to improve the quality of learning; and 2) Explores the forms of improving the quality of learning through sopimesem strategy. The result Sopimesem Strategy can improve the quality of learning; and 2) Improving the quality of learning is characterized by a form of awareness and understanding the importance of changing learning paradigms as outlined in the lesson plan (RPP) and the implementation of quality learning by utilizing and applying various strategies, models, methods and innovative media in a good quality learning process in the natural environment and social environment while still paying attention to the principles of learning that favor learning through, relating, experienting, actuating, contextual, transferring.